2021
DOI: 10.17305/bjbms.2021.5803
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA RP11-70C1.3 confers chemoresistance of breast cancer cells through miR-6736-3p/NRP-1 axis

Abstract: Chemoresistance remains a major obstacle for improving the clinical outcome of patients with breast cancer. Recently, long noncoding RNAs (lncRNAs) have been implicated in breast cancer chemoresistance. However, the function and underlying mechanism are still largely unknown. Using lncRNA microarray, we identified 122 upregulated and 475 downregulated lncRNAs that might be related to the breast cancer chemoresistance. Among them, RP11-70C1.3 was one of the most highly expressed lncRNAs. In breast cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies have shown that patients receiving long-term chemotherapy often develop chemoresistance [ 3 ]. For example, adriamycin (ADR) is an effective chemotherapeutic drug commonly used for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients receiving long-term chemotherapy often develop chemoresistance [ 3 ]. For example, adriamycin (ADR) is an effective chemotherapeutic drug commonly used for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5 The dysregulation of NRP-1 has been observed in several malignancies, such as breast cancer and bladder cancer. 6,7 Moreover, previous evidence has indicated that NRP-1 is highly expressed in GBM and plays a pivotal role in GBM progression. 8 High NRP-1 expression correlates with poor prognosis in GBM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropilin‐1 (NRP‐1) encodes a transmembrane glycoprotein that has been indicated to regulate axon guidance and nervous system development 5 . The dysregulation of NRP‐1 has been observed in several malignancies, such as breast cancer and bladder cancer 6,7 . Moreover, previous evidence has indicated that NRP‐1 is highly expressed in GBM and plays a pivotal role in GBM progression 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although lncRNAs possess no protein-coding ability, they are emerging as important players in gene silencing, transcriptional activation, chromosome modification, and intranuclear transport [6,7]. The contribution of lncRNAs in breast cancer has, therefore, received increasing attention [8][9][10]. Furthermore, many studies have provided evidence supporting lncRNA dysregulation in breast cancer and their significant roles [11][12][13].…”
Section: Introductionmentioning
confidence: 99%